Answer:
B. x = 3
Explanation:
The equation can be rearranged to ...
x² -6x +9 = 0
(x -3)² = 0 . . . .show as the square it is
x -3 = 0 . . . . . take the square root*
x = 3 . . . . . . . . add 3
___
* If the root were non-zero, there would be two of them: ±√( ). That would give rise to two possible values of x. That is not the case here, so there is only one solution.
_____
In the attached graph, the red curve represents the left side of the equation. The blue line represents the right side. They are equal at the one point where they intersect: (3, 9). That means when x=3, the equation becomes 9=9.